Pharmacokinetic study of precisely representative antidepressant, prokinetic, anti-inflammatory and anti-oxidative compounds from Fructus aurantii and Magnolia Bark. (5th January 2020) - Shi, Shaoqi; Yan, Han; Chen, Ying; Liu, Yalin; Zhang, Xueya; Xie, Ying; Xu, Jianjun; Wu, Lei; Chen, Ken; Shen, Xu; Ren, Ping; Huang, Xi
Abstract: Background: Currently, few herbal pharmacokinetic (PK) parameters have been applied successfully for therapeutic monitoring because of the complexity of consistency when there are multiple chemicals and efficacies. Purpose: The present study aims to evaluate the herbal PK properties by investigating the PK parameters of the 8 absorbed bioactive compounds (ABCs), which can represent its parent herbal holistic efficacy, to achieve a PK therapeutic monitoring of herbs. Method: First, we tested the hypothesis that the antidepressant and prokinetic effects and related anti-inflammation and anti-oxidation activity (APIO) by Fructus aurantii-Magnolia Bark (FM) formula are related to 8 compounds according to the absorbable evidence and the determined contents. Subsequently, stable and representative APIO from 8ABCs allowed us to develop a sensitive and selective liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for the simultaneous determination of 8 compounds following the oral administration of FM decoction (20 g/kg) in rats. Result: 8 compounds either including Meranzin hydrate (MH) or MH alone almost identically (8 compounds: 91.62–108.82%)or nearly(MH: 65.38–88.41%) replicated the parent formula FM in terms of efficacy for inducing APIO. Conclusion: This unifying strategy shows how multi-herb formulas pharmacokinetic therapeutic monitoring can be achieved by the method we established. Graphical abstract: Image 1 Highlights: The activity by Fructus aurantii-Magnolia Bark formula are related to 8 compounds. 8 compounds almost replicated the parent formula FM in terms of efficacy. The Pharmacokinetic of the 8 absorbed compounds in rats are studied.